Analiza przestrzenno-czasowa poziomu zanieczyszczenia środowiska - Biskup, Dariusz (Spatio-Temporal Pollution Analysis, 2007)
Environmental pollution can be analysed both spatially and temporally. In the spatial context, it is usually assumed that pollution correlation between monitoring sites is dependent on the distance between them. In the temporal analysis the correlation depends on the time lag between the measurements. The paper presents one of the methods of spatio-temporal modelling. It will be assumed that the pollution is a Gaussian process Y(s, t), where s denotes the location of the measurement site (sϵ R2), and t is the measurement time. The model is illustrated by the analysis of pollution in the Lower Silesia region. The parameters are estimated with the Bayesian approach using the Gibbs sampler.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1163, s. 55-64